2014
DOI: 10.13188/2331-8996.1000006
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition of Asteriscus maritimus (L.) Less. from Spain**

Abstract: The essential oil composition of different aerial parts (stems+leaves and flowers) of Asteriscus maritimus has been analysed by gas chromatography which was coupled with mass spectrometry. A total of 43 compounds have been identified from the different fractions studied, representing more than the 90% of the total oil for each one. Both aerial parts shared most of the main compounds although quantitative differences have been detected. The oils extracted from the stems and leaves showed α-pinene (27.5%) and p-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It is the main constituent of the volatile compounds of Piper longum L leaf (Hieu et al 2018) and an aroma compound found in Asteriscus maritimus (L.) Less. flowers from Spain and Xylopia phloiodora (Serhati 2010;Pala-Paul et al 2014) The second most abundant compound in the leaves of S. koetjape is 1H-Cyclopenta[1,3]cyclopropa[1,2]benzene. It is also known as β-cubebene (Groot and Schmidt 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is the main constituent of the volatile compounds of Piper longum L leaf (Hieu et al 2018) and an aroma compound found in Asteriscus maritimus (L.) Less. flowers from Spain and Xylopia phloiodora (Serhati 2010;Pala-Paul et al 2014) The second most abundant compound in the leaves of S. koetjape is 1H-Cyclopenta[1,3]cyclopropa[1,2]benzene. It is also known as β-cubebene (Groot and Schmidt 2016).…”
Section: Discussionmentioning
confidence: 99%